Analisis Kepatuhan Australia dan Indonesia Terhadap Code of Conduct dalam Hubungan Indonesia – Australia Sebagai Konsekuensi Adanya Penyadapan Tahun 2014-2019 - Kristanto, Gladys Ariella; Utomo, Tri Cahyo (Journal of International Relations, 2020)
Indonesia and Australia have an unique bilateral relations. After the espionage case by Australia revealed the Indonesia-Australia bilateral relations get into critical phase. Some cooperation have to stopped temporarily until there is a firm action from Australia such as the signing of a Code of Conduct. Meanwhile, if between Indonesia and Australia does not end this tension, both of them would have difficulty in carrying out their respective national interests. Both of them certainly have an interest especially in their defense and intelligence cooperation. Therefore, Indonesia - Australia agreed on the existence of a Code of Conduct in 2014 as a bridge in the process of restoring trust. This research uses the concept of compliance in determining the attitude of the two countries, as well as using the theory of institutional neo-liberalism in implementing international regimes. The results showed both countries adhere to the CoC based on factors of efficiency, national interests and norms